2007
DOI: 10.1071/bt06096
|View full text |Cite
|
Sign up to set email alerts
|

Grazing and fire in two subalpine peatlands

Abstract: The floristic composition and structure of peatland vegetation in adjoining subalpine catchments of the Bogong High Plains (north-eastern Victoria) were monitored between 1979 and 2006. Grazing by cattle had been excluded from one catchment since 1946, when it was fenced. Peatland vegetation in both catchments was partially burnt in a wildfire in 2003. Between 1979 and 1999, in the ungrazed peatland, the cover of Sphagnum cristatum Hampe and Baeckea gunniana Schauer increased and the cover of pools decreased, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
3
15
0
Order By: Relevance
“…Fire in some alpine environments may have long-lasting effects on some vegetation types, such as coniferous heaths in Tasmania (Kirkpatrick et al 2010), and hygrophilous shrubs that occur in Sphagnum wetlands (McDougall 2007). Fire in some alpine environments may have long-lasting effects on some vegetation types, such as coniferous heaths in Tasmania (Kirkpatrick et al 2010), and hygrophilous shrubs that occur in Sphagnum wetlands (McDougall 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Fire in some alpine environments may have long-lasting effects on some vegetation types, such as coniferous heaths in Tasmania (Kirkpatrick et al 2010), and hygrophilous shrubs that occur in Sphagnum wetlands (McDougall 2007). Fire in some alpine environments may have long-lasting effects on some vegetation types, such as coniferous heaths in Tasmania (Kirkpatrick et al 2010), and hygrophilous shrubs that occur in Sphagnum wetlands (McDougall 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although the wetland vegetation of the Australian Alps and the impacts of human activity are well described (Wahren, Papst & Williams, 1994;Wahren, Williams & Papst, 2001;McDougall, 2007;Lawrence et al, 2009), few comprehensive descriptions of the alpine freshwater fauna exist (Campbell, McKaige & Lake, 1986). There is some limited research on native fish, crayfish and the diverse and abundant insects of Australian alpine aquatic systems, but little to no information exists concerning the conspicuous and often highly abundant endemic amphipod and isopod crustaceans (Campbell et al, 1986;Swain, Chladil & Summers, 1994;Bradbury & Williams, 1999;Wilson & Keable, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Walker & Walker 1961; Tallis 1994), the drivers of pool formation and disappearance in Australia are poorly understood and the consequences of climate change for peat‐bog communities are far from certain. For instance, in a long‐term study of peat‐bog patterns on the Bogong High Plains, McDougall (2007) found that pools contracted despite above‐average precipitation. Such uncertainty and a changing climate highlight the need to carefully monitor these systems and avoid undertaking manipulative management (e.g.…”
Section: Discussionmentioning
confidence: 99%